2021
DOI: 10.1021/acs.jpcb.1c04087
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Gaussian Density Fluctuations from Microscopic to Macroscopic Volumes: Applications to Non-Polar Solute Hydration Thermodynamics

Abstract: The hydration of hydrophobic solutes is intimately related to the spontaneous formation of cavities in water through ambient density fluctuations. Information theory-based modeling and simulations have shown that water density fluctuations in small volumes are approximately Gaussian. For limiting cases of microscopic and macroscopic volumes, water density fluctuations are known exactly and are rigorously related to the density and isothermal compressibility of water. Here, we develop a theory—interpolated gaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…21 Recently, Ashbaugh, Vats, and Garde demonstrated that Gaussian fluctuations away from the critical point can be accurately captured simply from knowledge of water's density and compressibility, eliminating the need to invoke the water structure for describing molecular-scale hydrophobic hydration. 25 Quantifying and understanding the nature of p v (N) is an important focus of the work presented here.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 Recently, Ashbaugh, Vats, and Garde demonstrated that Gaussian fluctuations away from the critical point can be accurately captured simply from knowledge of water's density and compressibility, eliminating the need to invoke the water structure for describing molecular-scale hydrophobic hydration. 25 Quantifying and understanding the nature of p v (N) is an important focus of the work presented here.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 20 Assuming that the discrete Gaussian can be approximated using a continuous function, the excess chemical potential of an HS solute in water is where ⟨ n ⟩ = ρ(4 πR 3 /3) is the average number of waters residing within an observation sphere determined by the product of the solvent number density and volume, while χ = (⟨ n 2 ⟩ – ⟨ n ⟩ 2 /⟨ n ⟩ is the normalized solvent fluctuation in the observation sphere. While χ is determined by an integral over water’s radial distribution function performed over the observation volume, Ashbaugh, Vats, and Garde 21 recently developed an analytical expression for χ in spherical volumes that smoothly interpolates between the known microscopic and macroscopic limits to provide an excellent quantitative approximation away from the liquid–vapor critical point over all observation volume radii In this expression, κ T is the macroscopic solvent isothermal compressibility and η = πρd ww 3 /6 is the solvent packing fraction. The effective solvent diameter fitted to our simulation results is d ww = 2.663 Å, closely corresponding to the separation between water oxygens at which the radial distribution function first crosses one.…”
mentioning
confidence: 99%
“…The effective solvent diameter fitted to our simulation results is d ww = 2.663 Å, closely corresponding to the separation between water oxygens at which the radial distribution function first crosses one. 21 This expression enables eq 3 to predict the hydration free energies of HS solutes. While eq 4 interpolates the normalized cavity occupation fluctuations over all radii, the range of solute sizes for which eq 3 is applicable is limited due to its divergence below d ww /2, where the continuous distribution approximation breaks down and the necessity of considering higher-order moments of the distribution for larger solutes where interfacial contributions become important.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…And, the model gives interpretations of the observables on the basis of water structure and energies and solute size. Our work can be compared with a recent information theory-based model developed by Ashbaugh, Vats, and Garde, 54 which shows that the temperature dependence of hydrophobic hydration for hard-sphere solutes with varying sizes such as water’s density and compressibility, can be captured with only a few parameters. And Patel 55 also includes a solute–water attractive interaction in an information-theory-based model.…”
Section: Resultsmentioning
confidence: 99%